Proliferation of Lung Epithelial Cells Is Regulated by the Mechanisms of Autophagy Upon Exposure of Soots - Niranjan, Rituraj; Mishra, Kaushal Prasad; Tripathi, Sachchida Nand; Thakur, Ashwani Kumar (Frontiers in Cell and Developmental Biology, 2021)
Background Soots are known to cause many diseases in humans, but their underlying mechanisms of toxicity are still not known. Here, we report that soots induce cell proliferation of lung epithelial cells via modulating autophagy pathways. Results Fullerene soot and diesel exhaust particles (DEP) induced cell proliferation of lung epithelial, A549 cells via distinct autophagic mechanisms and did not cause cell death. Exposure of fullerene soot protected the cell death of A549 cells, caused by hydrogen peroxide, and inhibited LPS-induced autophagy. Fullerene soot co-localized with the autophagic proteins and inhibited starvation-induced autophagy (downregulated ATG-5, beclin-1, p62, and LC3 expressions) independent of its antioxidant properties. Similarly, it decreased the expression profile of autophagic genes and upregulated the proliferation-responsive gene, Ki-67, in mice. We observed that expressions of fullerene soot-responsive genes (Beclin-1, ATG-5, and p62) were reverted by Akt Inhibitor X, indicating an important role of the Akt pathway. At an elemental level, we found that elemental carbon of fullerene soot may be converted into organic carbon, as measured by OCEC, which may point fullerene soot as a source of carbon. On the other hand, DEP upregulated the expressions of autophagy genes. Akt Inhibitor X did not attenuate DEP-induced cell proliferation and autophagic response. However, an autophagic inhibitor, chloroquine, and significantly inhibited DEP-induced cell proliferation. Conclusion It can be said that distinct autophagic mechanisms are operational in cell proliferation of lung epithelial cells due to soots, which may be responsible for different diseases. Understanding the mechanism of these pathways provides some important targets, which can be utilized for the development of future therapeutics.